Comparison of HCG Levels in Reagents Temperature 25°C and 8°C Using ELISA Method : Perbandingan Kadar HCG Pada Reagen Suhu 25°C dan 8°C Menggunakan Metode ELISA - Telleng, Prisca Audra; Santosa, Budi; Kartika, Aprilia Indra (Universitas Muhammadiyah Sidoarjo, 2023)
HCG hormone is a hormone produced by the placenta in early pregnancy with the aim of maintaining pregnancy. The Elisa method is a method for examining HCG levels which has the principle of specific antigen and antibody reactions. The work stage in the laboratory that has the biggest error is in the pre-analytic stage reaching 60%, one of which is the reagent temperature. The ELISA method recommends the reagent temperature to be stored at 2-8°C and when used at 25°C. Examination reagents Elisa method uses reagents that use enzymes in the examination. Enzymes are very sensitive to temperature. This study aims to determine the ratio of HCG levels at reagent temperatures of 25°C & 8° using the ELISA method. This type of research is analytic supported by experiments and literature studies. Serum samples of 6 pregnant women were taken from the Kedungmundu Public Health Center using a limited population count formula. The examination was carried out by comparing the reagents at a temperature of 25°C and 8°C using 6 serums of pregnant women and in duplicate. Data analysis only used primary data and statistical tests were carried out using normality, homogeneity and T-Test tests. The average result at a temperature of 25°C was 380.851 and the average temperature of 8°C was 321.99 and the T-test statistic test showed p value = 0.469 and 0.470. Based on the results of the study, it can be concluded that there is an insignificant difference in the concentration of HCG by comparing the reagents at 25°C and 8°C.